2007
DOI: 10.1002/bdd.540
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in pharmacokinetic modeling

Abstract: A major part of the science of pharmacokinetics is the modeling of the underlying processes that contribute to drug disposition. The purpose of pharmacokinetic models is to summarize the knowledge gained in preclinical and clinical studies at various stages in drug development and to rationally guide future studies with the use of adequately predictive models. This review highlights a variety of recent advances in mechanistic pharmacokinetic modeling. It is aimed at a broad audience, and hence, an attempt was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…), and where traditional medicines are unregulated, or herbal remedies are commonly used. [13] Lastly, from a therapeutic perspective, there are standing concerns of adverse drug reactions (ADRs) between the conventional ARTs and type of CAM used [38,11,44], especially when most studies reported an adjunct use of CAM with ARTs. [31,45] This should also be a concern as the safety and risk factors of possible drug interactions are frequently ignored by PLWHA, as they are much focused on various expected benefits [42] as well as lack of knowledge on safety aspects.…”
Section: Discussionmentioning
confidence: 99%
“…), and where traditional medicines are unregulated, or herbal remedies are commonly used. [13] Lastly, from a therapeutic perspective, there are standing concerns of adverse drug reactions (ADRs) between the conventional ARTs and type of CAM used [38,11,44], especially when most studies reported an adjunct use of CAM with ARTs. [31,45] This should also be a concern as the safety and risk factors of possible drug interactions are frequently ignored by PLWHA, as they are much focused on various expected benefits [42] as well as lack of knowledge on safety aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, the pharmacokinetics of clenbuterol enantiomers in rats after i.v . administration of 2 mg/Kg of racemic clenbuterol showed higher concentration of S‐(+) enantiomer in plasma at 24 hrs., suggesting significantly different distribution and excretion of the enantiomers …”
Section: Resultsmentioning
confidence: 99%
“…administration of 2 mg/Kg of racemic clenbuterol showed higher concentration of S-(+) enantiomer in plasma at 24 hrs., suggesting significantly different distribution and excretion of the enantiomers. 31 However, in a recent study by Parr MC et al 3 a single dose of clenbuterol, either from a pharmaceutical preparation, or from meat containing clenbuterol (beef or liver) was studied in humans. Despite our data is not comparable to human results and the experimental design is different, this article is a pilot study which pretends to imitate the reality of doping cycles to which athletes are exposed and the effect of a constant consumption of contaminated meat.…”
Section: Application Of the Methods In The Experimental Animal Modelmentioning
confidence: 99%
“…Chirality may affect biological activity, so there is a need for the enantioseparation of these compounds. There are some publications on the chromatographic separation of flavanone, naringenin, and hesperetin enantiomers. These compounds are separated by prepared chiral cyclodextrin stationary phases or commercially available peptide‐based (Chiralpak AGP) or amylose/cellulose‐based (Chiralpak AD, Chiralcel OD) stationary phases.…”
mentioning
confidence: 99%
“…However, no information is available on the simultaneous separation for enantiomers of these three compounds (flavanone, naringenin, and hesperetin). Generally, most publications in the field of flavonoid enantioseparation are on the separation of a single compound enantiomer or on resolving more than one of them using different chiral columns and under different conditions, for example, using Chiralpak AD‐RH for hesperetin and Chiralcel OD‐RH for naringenin . Such a method could be useful, since multiple compounds, especially from one subclass, can occur in the presence of each other and simultaneous separation saves time and costs.…”
mentioning
confidence: 99%